Relevant information for the accountability of private institutions of social solidarity: Results from fieldwork - Helena Inácio; Alberto J. Costa; Ana Maria Bandeira; Augusta da Conceiç\~ao Santos Ferreira; Brízida Tomé; Carla Joaquim; Carlos Santos; Cristina Góis; Denise Curi; Deolinda Aparício Meira; Graça Maria do Carmo Azevedo; Mafalda Jesus; et al. (Economies, 2022)
The social economy (SE) has emerged as an interesting alternative for dealing with social problems. However, there are some concerns related to the abilities of these institutions regarding accountability. Thus, the present work aimed to determine if private social solidarity institutions (IPSS) are prepared to meet management requirements by increasing their accountability. In Portugal, IPSS are social economy organisations. Using an exploratory focus, we conducted qualitative research on 31 Portuguese IPSS. Interviews with those responsible for these entities took place between June and July 2019. The interviews were guided based on a semistructured script that was created based on a literature review. After content analysis, it was found that, in most of the institutions interviewed, the board does not use management tools, such as performance analysis, social impact assessments, strategic planning, and quality management systems, even though they recognise the importance of using them. This is due to the lack of access or knowledge about their use. In addition, the majority of the IPSS interviewed showed concern about the transparency and ethics of managers. Current strategic management practices are remarkably targeted at companies in the for-profit sector and can compromise the principles of investment in human and social issues.
Keywords: 330; accountability; management; nonprofit organisations; social economy; social solidarity institutions; transparency